2006
DOI: 10.1158/0008-5472.can-06-2224
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Expression of the Ubiquitin Carboxyl-Terminal Hydrolase L1 Gene in Human Airway Epithelium of Cigarette Smokers

Abstract: Neuroendocrine differentiation is a common feature of lung cancer and increased numbers of neuroendocrine cells and their peptides have been described in chronic smokers. To understand the effects of cigarette smoking on the gene expression profile of neuroendocrine cells, microarray analysis with TaqMan confirmation was used to assess airway epithelial samples obtained by fiberoptic bronchoscopy from 81 individuals [normal nonsmokers, normal smokers, smokers with early chronic obstructive lung disease (COPD),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 49 publications
8
67
1
1
Order By: Relevance
“…Second, previous studies have shown that replicate determinations of the levels of gene expression in the airway epithelium of the same subject gave highly reproducible levels of expression when assessed in the same individual over time 18 . Third, there is extensive data from our group and others of TaqMan confirmation of expression levels of genes in the airway epithelium determined by microarray methods and selected genes were confirmed in this study [18][19][20][29][30][31][32][33][34] . Fourth, assessment of an independent data set of nonsmokers and smokers verified a similar pattern of increase variability in this subset of the same genes.…”
Section: Reproducibility Of Measured Parameterssupporting
confidence: 62%
“…Second, previous studies have shown that replicate determinations of the levels of gene expression in the airway epithelium of the same subject gave highly reproducible levels of expression when assessed in the same individual over time 18 . Third, there is extensive data from our group and others of TaqMan confirmation of expression levels of genes in the airway epithelium determined by microarray methods and selected genes were confirmed in this study [18][19][20][29][30][31][32][33][34] . Fourth, assessment of an independent data set of nonsmokers and smokers verified a similar pattern of increase variability in this subset of the same genes.…”
Section: Reproducibility Of Measured Parameterssupporting
confidence: 62%
“…The gene expression arrays from a subset of the nonsmoker, healthy smoker, and COPD smoker groups used in this report have been used in previous reports (21,22), and the raw data from the arrays has been made available to the public (Gene Expression Omnibus [GEO] accession numbers GSE4498 and GSE5058). Neither of these studies reported on an expression of genes related to the Notch signaling pathway.…”
Section: Study Populationmentioning
confidence: 99%
“…All samples were assessed in triplicate at two different cDNA concentrations to ensure that amplification efficiency for the reference gene and gene of interest was the same. All PCR reactions were run in an Applied Biosystems Sequence Detection System 7500 as previously described (21,22).…”
Section: Taqman Real-time Reverse Transcriptase-pcrmentioning
confidence: 99%
“…Interestingly, UCH-L1 expression is upregulated in PC1/3 cells (online supplementary figure S1c and table S2). As previously stated, UCH-L1 is a neuroendocrine cell-specific protein used as a marker in assessing lung cancer [25].…”
Section: Discussionmentioning
confidence: 98%
“…Surprisingly, PC1/3 is also expressed in goblet and ciliated cells in the nasal polyp epithelium. CAROLAN et al [25] have shown that ubiquitin carboxyl-terminal hydrolase (UCH)-L1, a marker of neuroendocrine cells, is expressed only in neuroendocrine cells of the airway epithelium in nonsmokers, while in smokers UCH-L1 is also upregulated in ciliated epithelial cells. In line with these studies, we suggest that both goblet cells and ciliated cells can transdifferentiate to other epithelial cells.…”
Section: Discussionmentioning
confidence: 99%